Interpersonal Communication Da’i; Analysis of Da'wah Styles on YouTube - Siti Zaida Hanum; Surawan; Muhammad Al Farizi; Sarimah Awang (Mediakita, 2023)
Along with the times, the da'i began to use social media as a medium of da'wah calling for good and forbidding evil. One of the most popular da'wah content creators today is Habib Jafar. Researchers are interested in analyzing the preaching style of Habib Jafar through YouTube in conveying the context of peaceful Islam because he is a da'i who is suitable to be juxtaposed with religious figures other than Islam, and audiences can universally accept his da'wah. Habib Jafar's da'wah content can attract the attention of millennials in the digital era to keep them enthusiastic about following studies on Islam. This study uses a qualitative research approach with library research methods. The data sources used are primary data sources and secondary data sources. The subject of this research is Habib Jafar, and the object of this research is Habib Jafar's da'wah style. The result of this research is to know the process of implementing Habib Jafar's da'wah to millennials who are armed with communication styles, depth of intellectual competence, open thinking, and positive views on the audience as well as the success of Habib Jafar in carrying out interfaith da'wah which is the result of a combination of communication skills and understanding the characteristics of communication opponents and having flexibility in delivering da'wah so that the messages conveyed can be adequately described.